Impact of global value chain on China’s automobile industry upgrading: The mediating effect of technology investment and moderating effect of foreign direct investment - Tingting, Sun; Muhammad Asraf, Abdullah (MAG Scholar, 2025)
The automobile industry is a cornerstone of China’s economy, with its upgrading significantly influencing overall economic growth. Global value chain (GVC), as a framework that connects global markets and production resources, substantially impacts an industry’s international competitiveness. This study employs the Malmquist Productivity Index based on the Data Envelopment Analysis (DEA) method to assess China’s automobile industry (CAI). Additionally, a system Generalized Method of Moments (GMM) approach is utilized to investigate the influence of GVC on the upgrading process while further examining the mediating and moderating roles of technological innovation and foreign direct investment (FDI). The findings show that GVC has a significant negative effect on upgrading CAI, with technology investment acting as a mediating factor; specifically, GVC hinders industry upgrading by inhibiting technology investment. Furthermore, FDI mitigates the negative impact of GVC on the upgrading of CAI. Based on these findings, this study offers policy implications to promote the upgrading of CAI.